Nahw Wajh Jadīd: al-Muḥāwala fī Tarsīkh Maqāṣid al-Sunna al-Nabawiyya bi Indūnīsiyā [Toward a New Perspective: An Attempt in Strenghtening Maqāṣid al-Sunnah in Indonesia] - Abdul Mufid (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
The notion that the Qur'an is always relevant all the time and space can also be applied to hadith. Its due to hadith itself, in fact, is an embodiment of Qur’anic teachings which means it comes from God’s revelation-Allah directly. Therefore, the slogan should not only be comprehended on rhetoric limitation, but rather be applied in religious life, national life, and state of life regularly. Considering the length of time and space in which starting from the emergence of Hadith until nowadays, of course, the gap between the hadith and the reader space was founded. Furthermore, added with the dark stories and dark histories in the past such as the phenomenon of hadith forgery, of course, it adds to the tension and the extent of the gap. According to the fact as mentioned, lead the researcher to conduct this study. Moreover, as a form of problem-solving to minimize the gaps, it really necessary attempts. Maintaining the values of hadith and the main objectives of hadith is the answer that can be pursued through two important attempts, there are: The first one is contextualization and revitalization of the hadith message. This step is carried out to reveal the fundamental message of the hadith in order to answer the gap as well as a bridge time and space, and the second one is applying it to the ulumul hadith principles, such as asbabul wurud and also is influenced with local wisdom. Furthermore, the scope of this study not only limited to focusing on studying the reconstruction of interpretations of hadith but also includes information on how to produce meaning and apply the concept of contextualization of the hadith's message. In addition, studying of how to explain the contextualization of hadith with the context of contemporary Indonesia through the reinterpretation and reproduction of the meanings of three phenomena; 1) the unification of the hijriyah calendar in Indonesia, 2) the reading of sighat ta'liq for the bridegroom, and 3) the inheritance of different religions.